Biomass tannic acid intermediated surface functionalization of ammonium polyphosphate for enhancing fire safety and smoke suppression of thermoplastic polyurethane. (3rd April 2023) - Wang, Shasha; Fang, Quan; Liu, Chao; Zhang, Jie; Jiang, Yaqiang; Huang, Yi; Yang, Man; Tan, Zhezhe; He, Yunlong; Ji, Ben; Qi, Congrui; Chen, Yue
Graphical abstract: Highlights: FeOOH combined with PDMS was employed to construct HAPP via a simple strategy. Biomass TA as a universal linker was applied to fabricate HAPP. Hierarchical structure on HAPP leaded to an excellent compatibility with TPU. HAPP endowed TPU with satisfactory fire-retardant and smoke suppression properties. Abstract: Hierarchical ammonium polyphosphate (HAPP) was designed and fabricated by means of a simple strategy. FeOOH nanoparticles were decorated onto the APP surface based on the universal surface-adaptive interfacial adhesion of tannic acid (TA) and then modified by using polydimethylsiloxane (PDMS) to obtain HAPP. Owing to unique microstructure, the introduction of HAPP not only endows thermoplastic polyurethane (TPU) with admirable flame retardancy, but also presents excellent interfacial compatibility. The Young's modulus, tensile strength and elongation at break of TPU composite with 5 wt% HAPP are increased by 4.3 %, 11.0 % and 16.6 %, respectively, relative to the values for TPU composite containing 5 wt% APP. Furthermore, TPU composite including 5 wt% HAPP achieve a UL-94 V-0 rating with the maximum limiting oxygen index value. Compared to those of TPU, the peak heat release rate, total heat release and total smoke production of TPU composite with 5 wt% HAPP are remarkably decreased with the reduction of 57.7 %, 23.1 % and 82.3 %, respectively. The proposed combination of transition metal oxides and low surface energy material is expected to reinforce the interfacial adhesion force between the APP and the polymer matrix and then inspires new strategies to construct polymer composites with excellent comprehensive properties.